Participation in Forest and Conservation Management - World Bank (Washington, DC, 2012)
The participation of local communities and other stakeholders in managing forestry and conservation projects can help to improve forest productivity, alleviate poverty, enhance environmental sustainability, and make rules governing forest access more enforceable. Introducing participatory management depends on government commitment; and it requires time and resources to develop consensus among stakeholders, establish new institutional arrangements, decentralize finance and administration, ensure appropriate rules and incentives for local involvement, and build organizational capacity at the local level.